2001
DOI: 10.1093/jjco/hye060
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Outpatient Schedule of Paclitaxel in Patients with Previously Untreated Metastatic, Measurable Adenocarcinoma of the Stomach

Abstract: Paclitaxel exhibited minimal activity in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…In support of this hypothesis, BubR1 was found to be overexpressed in a cohort of 43 gastric carcinomas (Grabsch et al, 2003). It is noteworthy that paclitaxel failed in clinical trials in patients with gastric carcinoma (Garcia et al, 2001). An overactive mitotic checkpoint may contribute to paclitaxel resistance in gastric carcinomas, among others.…”
Section: Discussionmentioning
confidence: 74%
“…In support of this hypothesis, BubR1 was found to be overexpressed in a cohort of 43 gastric carcinomas (Grabsch et al, 2003). It is noteworthy that paclitaxel failed in clinical trials in patients with gastric carcinoma (Garcia et al, 2001). An overactive mitotic checkpoint may contribute to paclitaxel resistance in gastric carcinomas, among others.…”
Section: Discussionmentioning
confidence: 74%
“…With paclitaxel used as a single agent, RRs of 11% and median survivals of 3 and 6.5 months have been reported [21][22][23]. In combination with 5-FU or carboplatin, trials have indicated a median survival of 9-11 months [23][24][25].…”
Section: Chemotherapy In Advanced Gastric Cancermentioning
confidence: 99%
“…Paclitaxel (Taxol s ; Bristol -Meyers Squibb Company, Princeton, NJ, USA), the prototype taxane compound that interferes with tubulin assembly (Rowinsky et al, 1990), has been studied extensively in patients with previously treated or untreated gastric cancer. As a single agent, paclitaxel induced responses in 11 -17% of previously untreated patients (Ajani et al, 1998;Garcia et al, 2001), and activity was also seen in previously treated patients (Cascinu et al, 1998;Yamada et al, 2001). The in vitro cytotoxic effects of paclitaxel plus 5-FU were found to depend on the schedule used, in that application of paclitaxel before 5-FU enhanced cytotoxicity, whereas the application of paclitaxel after 5-FU resulted in a less than additive cytotoxic effect (Kano et al, 1996).…”
mentioning
confidence: 99%